Kajian Sense of Place pada Street Coffee di Kawasan Kotabaru, Yogyakarta - Ahmad Fatah Haidar Rahmat (Universitas Sebelas Maret Surakarta, 2025)
A Study ofSense of Place at Street Coffee in the Kotabaru Area, YogyakartaStreet coffee in Kotabaru has become a new coffee culture in Yogyakarta. This study aims to in-depth examine the contribution of street coffee to the sense of place in Kotabaru through a qualitative approach. Data collection was conducted through field observations and in-depth interviews with sellers and buyers at Kotabaru's street coffee shops. Data analysis was conducted using thematic analysis based on the codification and categorization of interview results. The results of this study indicate that the sense of place in Kotabaru's street coffee shops is formed by a combination of the uniqueness of Kotabaru's outdoor space, economic and social values, and attachment. However, street coffee raises issues that require stakeholder intervention to create synergy between contemporary street coffee activities and the cultural heritage area of Kotabaru.